Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00449-012-0812-3
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of the α-amylase of Bacillus amyloliquifaciens TSWK1-1 for the improved biocatalytic properties and solvent tolerance

Abstract: The α-amylase of Bacillus amyloliquifaciens TSWK1-1 (GenBank Number, GQ121033) was immobilized by various methods, including ionic binding with DEAE cellulose, covalent coupling with gelatin and entrapment in polyacrylamide and agar. The immobilization of the purified enzyme was most effective with the DEAE cellulose followed by gelatin, agar and polyacrylamide. The K m increased, while V max decreased upon immobilization on various supports. The temperature and pH profiles broadened, while thermostability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…5a, the optimal screening efficiency was achieved at pH 7.0. The optimum pH in screening procedure was coincidence with the report of free α-amylase [30].…”
Section: Optimization Of Screening Conditionssupporting
confidence: 72%
“…5a, the optimal screening efficiency was achieved at pH 7.0. The optimum pH in screening procedure was coincidence with the report of free α-amylase [30].…”
Section: Optimization Of Screening Conditionssupporting
confidence: 72%
“…The enzyme α ‐amylase has been immobilized by several methods, namely adsorption , entrapment , cross linking , and covalent binding . Among these, covalent binding is very effective in retaining the enzyme activity and provides a maximum rigidity and also prevents enzyme from unfolding upon heating or in the presence of a denaturant .…”
Section: Introductionmentioning
confidence: 99%
“…According to Ewadh and Al‐Khafaji, the immobilization of enzymes onto gelatin primarily occurs via crosslinking between the free amino groups of the carrier and the enzyme molecule with crosslinking agents, which form a covalent bond. Kikani et al ., for instance, studied the covalent coupling of α‐amylase from Bacillus amyloliquifaciens TSWK1‐1 with gelatin, using glutaraldehyde as a crosslinker. The authors observed that the thermal and pH stabilities were significantly increased after immobilization.…”
Section: Renewable Polymeric Matrixes Used For Enzyme Immobilizationmentioning
confidence: 99%